Hubungan Antara Harga Diri Dan Stres Dengan Psychological Well Being Pada Remaja Panti Asuhan Tanjung Barat Di Jakarta - Marshinta Rotua Sitorus; Anastasia Sri Maryatm (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This study aims to determine the relationship between Self-Esteem and StresLevel with Psychological Well Being in adolescents at the Tanjung BaratOrphanage. The sampling method uses the total sampling technique. The numberof samples used in this study were 50 people with the characteristics of boys andgirls aged 13 years - 17 years. The data collection method itself consists of apsychological well being scale, a self-esteem scale, and a stres level scale. Theresults of data analysis with bivariate correlation showed that there was asignificant relationship between self-esteem and psychological well being with acorrelation coefficient of r = 0.404 with p = 0.004 (p <0.05), there was arelationship between stres and psychological well being with a correlationcoefficient of r = -0.431 with p = 0.002 (p <0.05). The results of data analysis withmultivariate correlation showed r = 0.583 with p = 0.000 (p <0.05), so there is asignificant relationship between self-esteem and stres with psychological wellbeing among adolescents at the Tanjung Barat Orphanage. The coefficient ofdetermination or R Square is 0.340, which means the contribution of self-esteemalong with stres levels with psychological well being. Based on the output of theStepwise Method, self-esteem contributes to psychological well being by 15.4% (RSquare Change 0.154). Meanwhile, the stres contribution to psychological wellbeing was 18.5% (R Square Change 0.185).